26 What drives rapid progression to ESRD in patients with lupus nephritis?. (6th April 2022) - Urowitz, Murray
Abstract : Lupus nephritis (LN) affects up to 40% of patients with systemic lupus erythematosus (SLE) and leads to end stage kidney disease (ESRD) in 17–33% after 10 years. 1 We have investigated a number of factors that have been shown to predispose to a more rapid progression to ESRD, including time to initial response to conventional therapy, number of flares during follow-up, duration of immunosuppressive therapy, unusual histologic patterns and patient compliance. In the Toronto Lupus Cohort of 418 patients with LN, 209 (50%) achieved remission within the first year from LN diagnosis, 102 (24.4%) within the 2nd and 3rd years, 70 (16.7%) after 3 years and 37 (8.9%) never achieved remission. Sixty-six patients (15.8%) developed advanced chronic kidney disease after 9.5 years on average. The 66 patients who progressed to ESRD had a longer time to complete remission (3.0 ± 3.4 vs 1.6 ± 2.1 yrs), more often had two or more flares (40 (60.6%) vs 117 (33.2%) and had a shorter median time on immunosuppressants from complete remission to outcome (2 yrs (0–7) versus 4 yrs (0–8)). These factors remained independently significant in a multivariable analysis accounting for multiple other relevant factors. Catastrophic progression to ESRD was also associated with unusual histologic patterns. Examples of these included thrombotic microangiopathy, interstitial inflammation added to the classic ISN classes, collapsing glomerulopathy, concomitant anti-GBM nephropathy and poor patient compliance. These findings emphasize the importance of achieving early remission as well as flare prevention with prolonged immunosuppressive use and attention to patient compliance to maximise renal survival in LN. Reference: Tektonidou MG, et al . Risk of end-stage renal disease in patients with lupus nephritis, 1971–2015: a systematic review and bayesian meta-analysis. Arthritis Rheumatol 2016 Jun;68 (6):1432–1441. Learning Objectives: Explain that shorter time to remission of LN protects against rapid progression to ESRD Explain that preventing flares in LN protects against rapid progression to ESRD Explain that longer duration of immunosuppressive therapy in LN protects against rapid progression to ESRD Describe the unusual features of LN that might lead to catastrophic progression to ESRD